The new emotional intelligence - Bradberry, Travis ([Bruyere Publishing], 2025)
The New Emotional Intelligence by Dr. Travis Bradberry offers a science-backed, step-by-step program with 60 practical strategies to boost emotional intelligence across self-awareness, self-management, social awareness, and relationship skills. Featuring an exclusive EQ test, personalized results, and online tools, the book helps readers identify growth areas, track progress, and unlock their full potential.